2017
DOI: 10.2196/jmir.7037
|View full text |Cite
|
Sign up to set email alerts
|

High Level of Integration in Integrated Disease Management Leads to Higher Usage in the e-Vita Study: Self-Management of Chronic Obstructive Pulmonary Disease With Web-Based Platforms in a Parallel Cohort Design

Abstract: BackgroundWorldwide, nearly 3 million people die of chronic obstructive pulmonary disease (COPD) every year. Integrated disease management (IDM) improves disease-specific quality of life and exercise capacity for people with COPD, but can also reduce hospital admissions and hospital days. Self-management of COPD through eHealth interventions has shown to be an effective method to improve the quality and efficiency of IDM in several settings, but it remains unknown which factors influence usage of eHealth and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 40 publications
4
31
0
2
Order By: Relevance
“…In our study, 34% of the patients logged on, which was an improvement from the 11% found in the study by Roelofsen et al (2014) on the former version of e-Vita. The trainings about the functionalities of the platform seemed necessary to familiarize patients with the platform [45,47,48]. This may also have decreased the threshold for patients to visit this platform and may have helped patients and PNs to feel the gains of using it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, 34% of the patients logged on, which was an improvement from the 11% found in the study by Roelofsen et al (2014) on the former version of e-Vita. The trainings about the functionalities of the platform seemed necessary to familiarize patients with the platform [45,47,48]. This may also have decreased the threshold for patients to visit this platform and may have helped patients and PNs to feel the gains of using it.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible causes for the increase in platform usage could be the visual and technical improvements of the platform. In addition, bended care, where digital health and usual care are integrated, is likely to lead to increased use of an online program for patients with COPD [48]. Patients with diabetes log on to platforms for various reasons.…”
Section: Discussionmentioning
confidence: 99%
“…In a patient population with more severe COPD (patient-data meta-analysis from 2016), self-management interventions improved health-related QoL at 12 months but not at 6 months [ 52 ]; this confirms our observation that long-term use of platforms is necessary for an effect on health status. In our research, the platforms are probably not sufficiently customized to the wishes or needs of COPD patients to provide sufficient motivation to use the platform on a regular basis for a longer period; in our e-Vita study, a significant number of users stopped using the platforms (attrition) [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 702 eligible patients, 30.6% were willing to participate and provided informed consent, and 61.4% of the participants dropped out during follow-up. Even though the nonparticipants did not differ in age or gender from the participants [ 32 ], caution is required when generalizing these results to general practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation